Evaluating the role of anxiety sensitivity in barriers to cessation and reasons for quitting among smokers with asthma. Issue 2 (17th February 2016) - McLeish, Alison C.; Johnson, Adrienne L.; Avallone, Kimberly M.; Zvolensky, Michael J.
Abstract : The aim of the present study was to examine the unique predictive ability of anxiety sensitivity (AS) in terms of perceived barriers to cessation and smoking cessation motives among daily smokers with asthma ( n = 125, 54% male, M age = 37.7 years, SD = 12.1). As hypothesized, after controlling for the effects of race, asthma control, negative affect, and smoking rate, AS significantly predicted greater barriers to cessation, and reasons for quitting related to health concerns and self-control. Contrary to hypotheses, AS did not significantly predict external reasons for quitting. These findings suggest that smokers with asthma who are fearful of physiological arousal may be a particularly 'at-risk' population for smoking cessation difficulties due, in part, to greater perceived barriers to cessation. Interventions focused on enhancing intrinsic motivation for quitting and reducing AS may be most effective for this population.